Abrogation of VEGF expression in human head and neck squamous cell carcinoma decreases angiogenic activity in vitro and in vivo - Riedel, Frank; Götte, Karl; Li, Mengfeng; Hörmann, Karl; Grandis, Jennifer R. (International journal of oncology, 2003)
Angiogenesis is increased in various human cancers, including head and neck squamous cell carcinoma (HNSCC), and correlates with tumor progression and metastasis. Vascular endothelial growth factor (VEGF) has been shown to be a key regulator of angiogenesis. We determined whether VEGF antisense oligonucleotide treatment can decrease angiogenic activity of HNSCC cell lines in vitro and of HNSCC xenografts in vivo. Established human HNSCC cell lines were screened for VEGF expression at both mRNA and protein levels. By using a 21-mer antisense phosphorothioate oligonucleotide targeting the translation start site of human VEGF mRNA, we examined modulation of VEGF expression in cell line supernatants by capture ELISA, and in cell lysates by Western blotting. Human umbilica vein endothelial cells (HUVEC) were grown in conditioned medium produced from the treated tumor cells. Endothelial cell (EC) proliferation was determined by cell count and EC migration was measured using a modified Boyden chamber. Mice with HNSCC xenografts were treated with PBS, VEGF antisense or sense oligonucleotides (10 mg/kg; i.p. injection), respectively and tumor volumes were measured for 5 weeks. VEGF antisense oligonucleotide treatment resulted in a significant reduction of VEGF protein expression compared to sense control. Although the growth rate of the tumor cell lines was not affected, addition of conditioned medium from VEGF antisense-treated tumor cells resulted in decrease of endothelial cell proliferation and migration. VEGF antisense oligonucleotide treatment of HNSCC xenografts resulted in a significant tumor growth suppression. These results suggest that downmodulation of VEGF using antisense oligonucleotides may be a potential therapy for the inhibition of angiogenesis in HNSCC.